METHODOLOGICAL CONTRIBUTION IN THE FIELD OF MOUNTAIN LEISURE ACTIVITIES PRACTICING CASE STUDY: SCRAMBLING IN HIGH TATRAS - BÎCA, Ioan; ZANCA, Raoul; SCHUSTER, Eduard (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2019)
Mountain leisure activities attract many participants because they are beneficial for health, maintain fitness, induce the feeling of performance and are spectacular. Among these activities, stands scrambling, which is part of the mountaineering and it is practice on the rock exposed surfaces (walls, ridges, chimneys, gully). One of the areas that offer excellent conditions for practicing scrambling is High Tatras (Vysoke Tatry) in Slovakia, where granite and gneiss rocks have created an attractive and favorable microrelief for this activity. This study aims at carrying out experimental methodological researches on the route Velička Dolina-Velicky zlab-Gerlachovský peak- Dolina-batizovsle Žlab-Batizovska Dolina-Batizovske Pleso-Sliezsky Dom regarding scrambling organization activity and mentation of specific climbing techniques in correlation with geologic factors (rocks, landforms). The subjects of this experiment were a group of students from the Faculty of Geography, from Babes-Bolyai University Cluj-Napoca (Romania), Tourism Geography specialization, without previous mountaineering experience on stony ground. REZUMAT. Contribuții metodologice în domeniul practicării activităților agrementale montane. Studiu de caz: Scrambling în Tatra Înaltă. Activitățile agrementale montane atrag numeroși participanți, deoarece sunt benefici pentru sănătate, mențin condiția fizică, induc sentimentul de performanți și sunt spectaculoase. Dintre aceste activități, se remarcă scramblingul, care face parte din mountaineering și se practică pe suprafețe cu roci expuse (pereți, creste, hornuri, gullys). Unul dintre arealele care oferă condiții deosebite pentru practicarea scramblingului este High Tatras din Slovacia, unde rocile granitice și gnaisice au creat un microrelief atractiv și favorabil acestei activități. Studiul de față are ca obiectiv efectuarea unor cercetări experimentale metodologice pe traseul Velicka Dolina-Velicky zlab-Gerlachovsky peak-Batizovske zlab-Batizovska Dolina-batizovsle Pleso-Sliezsky Dom privind organizarea activității de scrambling și aplicarea tehnicilor specifice de cățărare în corelație cu factorul geologico-geografic (rocă, microrelief). Subiecții acestui experiment au fost un grup de studenți de la Facultatea de Geografie a Universității Babeș-Bolyai din Cluj-Napoca (România) specializarea Geografia Turismului, fără experiențe montane anterioare pe terenuri stâncoase. Cuvinte-cheie: activități agrementale active, scrambling, escaladă, turism montan, Gerlachovsky.